1-alpha-hydroxycholecalciferol for renal osteodystrophy. Issue 6089 (17th September 1977) - Brownjohn, A M; Goodwin, F J; Hately, W; Marsh, F P; O'Riordan, J L; Papapoulos, S E
Abstract : Fourteen patients with renal osteodystrophy were treated for at least one year with 1-alpha-hydroxycholecalciferol (1-alpha-OHD3) in a dose varying from 1 microgram/week to 3 microgram/day. Plasma calcium and inorganic phosphorus concentrations increased significantly. The plasma alkaline phosphatase concentration fell in 11 of the 12 patients in whom it was initially raised and returned to normal in seven. Serum parathyroid hormone concentrations were initially raised in all patients, but they decreased significantly with treatment and became normal in eight patients within one year. The 10 patients with radiological abnormalities showed some improvement. Hypercalcaemia occurred in 11 patients, and necessitated a reduction in the dose of 1-alpha-OHD3 in some. 1-alpha-OHD3 was effective in reducing the biochemical and radiological abnormalities of renal osteodystrophy, but it should be used wtih care, and plasma calcium concentrations should be monitored.